2012
DOI: 10.1021/la303437k
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic, Kinetic, Surface pKa, and Structural Aspects of Self-Assembled Monolayers of Thio Compounds on Gold

Abstract: The thermodynamic and kinetic aspects of the formation of self-assembled monolayers (SAMs) of thio compounds on gold have been studied via electrochemical and quartz crystal microbalance (QCM) techniques. The data indicate that the adsorption process involves a significant free energy of adsorption (ΔG° = -36.43 kJ/mol) and that there are slight repulsive interactions between adjacent molecules on the surface. A method for the calculation of surface pK(a) values of molecules containing more than one protonatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Although thiol-based SAMs on functionalized gold electrodes are an attractive method for surface modification and organometallic coordination, the linker to Au surface bond is rather weak and can be prone to chemical attack and reductive desorption . The strength of the interaction between the gold surface, thiol headgroup, and ordering in the alkyl chain is typically on the order of less than 40 kcal/mol. Therefore, Pyr-1 was chosen as a grafting substrate under the presumption that the oxidation of the dimethylamine component of the molecule would result in covalent attachment to the electrode surface. This electrode modification technique has been previously observed for primary, secondary, and tertiary amines on GC and Au electrodes. The pyridine headgroup of the Pyr-1 linker is proposed to act as an axial ligand to coordinate the Py 2 XPFe complex, as has been observed previously with iron–phthalocyanine on multiwalled carbon nanotubes (MWCNTs) and other iron–porphyrin complexes with imidazole-terminated linkers. , Indeed, the linker Pyr-1 was found to function as an effective grafting substrate in acetonitrile (MeCN) as one-electron oxidation at relatively mild potentials (approximately 0.9 V vs Ag/AgCl) on Au gives rise to an irreversible wave at slow scan rates (25 mV/s) proceeding concurrently with gold oxide formation, while successive scanning results in lower faradaic currents (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…Although thiol-based SAMs on functionalized gold electrodes are an attractive method for surface modification and organometallic coordination, the linker to Au surface bond is rather weak and can be prone to chemical attack and reductive desorption . The strength of the interaction between the gold surface, thiol headgroup, and ordering in the alkyl chain is typically on the order of less than 40 kcal/mol. Therefore, Pyr-1 was chosen as a grafting substrate under the presumption that the oxidation of the dimethylamine component of the molecule would result in covalent attachment to the electrode surface. This electrode modification technique has been previously observed for primary, secondary, and tertiary amines on GC and Au electrodes. The pyridine headgroup of the Pyr-1 linker is proposed to act as an axial ligand to coordinate the Py 2 XPFe complex, as has been observed previously with iron–phthalocyanine on multiwalled carbon nanotubes (MWCNTs) and other iron–porphyrin complexes with imidazole-terminated linkers. , Indeed, the linker Pyr-1 was found to function as an effective grafting substrate in acetonitrile (MeCN) as one-electron oxidation at relatively mild potentials (approximately 0.9 V vs Ag/AgCl) on Au gives rise to an irreversible wave at slow scan rates (25 mV/s) proceeding concurrently with gold oxide formation, while successive scanning results in lower faradaic currents (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…The origin of the cathodic contributions at potential zone II and its complementary contributions at zone III is not clear. It has been proposed for other aromatic thiols that the adsorption process induces activation of the oxidative cleavage of the S-C bond, with the resulting formation of an adlayer composed of atomic and oligomeric forms of sulfur [33,55,[59][60][61].…”
Section: Voltamperometric Characterization Of 2-mna Samsmentioning
confidence: 99%
“…It is generally observed that the measured pK a of surface-confined molecules may differ significantly from the corresponding value for the same molecule in solution, which is ascribed to the influence of the local environment [19,20]. Acid/base ionization behavior of x-functionalized SAMs of alkanethiols as well as of aromatic/heteroaromatic functionalized SAMs has been studied [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. Nevertheless, the behavior of the -COOH and pyridinic groups as well as monolayer structure, orientation and electrochemical characteristics of SAMs of 2-mercaptonicotinic acid (2-MNA) on gold have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The surface p K a values obtained by using an FNAA were compared to those reported in the literature (shown in Table ). This shows that different surface p K a values have been found for the same chemically modified gold surfaces when using different methods (e.g., Fourier-transform surface-enhanced Raman scattering, chemical force microscopy, and faradaic impedance titration ,,,, ). Therefore, these literature values illustrate that the determination of surface p K a values is not straightforward and the outcome may be dependent on the method used (several methods have different measurement principles).…”
Section: Discussionmentioning
confidence: 90%
“…So far, the FNAA has been used to determine the p K a of silicon surfaces modified with amine groups (APTES), carboxylic groups, and pyridine groups. , Besides, this method was used to analyze more complex surfaces (i.e., determination and design of the isoelectric point of chemically modified silicon surfaces) . Furthermore, since most methods are not suitable to detect more than one p K a values, the FNAA could be an attractive method to analyze surfaces that have more than one p K a values . So far, the FNAA has not been used to determine the p K a of surfaces other than silicon.…”
Section: Introductionmentioning
confidence: 99%